Disseminated gonococcal infection in a homosexual man diagnosed by nucleic acid amplification testing from a skin lesion swab. Issue 5 (22nd September 2008) - Read, P; Abbott, R; Pantelidis, P; Peters, B S; White, J A
Abstract : Disseminated gonococcal infection (DGI) often presents a diagnostic challenge. Through the novel application of molecular technology, a case is presented that suggests how the diagnostic sensitivity for this systemic complication of gonococcal infection can be improved. In a typical case of DGI seen in a homosexual man in whom all mucosal and blood specimens were culture negative, nucleic acid amplification testing (NAAT) helped to confirm the diagnosis. Both throat and skin lesion specimens tested positive for gonococcal DNA and this was confirmed with a supplementary porA pseudogene NAAT. The use of adjuvant NAAT assessment is recommended as part of the diagnostic work-up for suspected DGI cases.